Profil Keterampilan Berpikir Kritis Peserta Didik Pada Pembelajaran Biologi - Muhammad Syafiq Hilmie (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This study aims to determine the profile of critical thinking skills of students at SMA Negeri 1 Singaparna in biology learning. The research method used is quantitative descriptive. The sample used was 114 students in class X. The instrument used in this study was a descriptive test consisting of 9 questions referring to the critical thinking indicators developed by Ennis, namely providing simple explanations, building basic skills, concluding, providing further explanations, and arranging strategies and tactics. The data analysis technique used in this study was the reliability and validity of the instrument to ensure that the critical thinking skills measurement instrument used was reliable and valid. The results of the study of students' critical thinking skills on the indicator providing a simple explanation of 47.3% with a low category, the indicator providing a simple explanation shows a percentage of 65.3% with a medium category, the indicator concluding shows a percentage of 59.3% with a low category, the indicator providing further explanation shows a percentage of 55.3% with a low category, the indicator arranging strategies and tactics shows a percentage of 50.3% with a low category. Based on these data, it can be seen that the average critical thinking skills of students is 55.5% which can be categorized as low critical thinking skills. The results of the study can provide a significant contribution in improving the quality of biology education at SMA Negeri 1 Singaparna, by encouraging the development of students' critical thinking skills that will be useful for them in academic environments.